2021
DOI: 10.1016/j.esxm.2021.100465
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual Morbidity in Women With Ovarian Cancer: Evaluation by Germline BRCA Gene Mutational Status

Abstract: Introduction: Up to 75% of women with ovarian cancer experience psychosexual morbidity and approximately 15−20% of women with ovarian cancer have a germline BRCA1/2 mutation (gBRCAm). However, psychosexual morbidity remains unexplored in women with gBRCAm ovarian cancer. Aim: Given their younger age, genetic diagnosis, breast cancer risk, and increased prevalence of surgicallyinduced menopause, we aim to assess whether women with gBRCAm ovarian cancer experience distinct psychosexual morbidity. Methods: Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…It is more likely that female cancer patients will suffer from depression as they are more susceptible to it [ 10 ]. Studies on breast, cervical, and ovarian cancer patients showed that those patients had a high prevalence of depression and anxiety disorders [ [11] , [12] , [13] , [14] ]. Nevertheless, depression is often neglected, and the majority of cancer patients do not receive adequate treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is more likely that female cancer patients will suffer from depression as they are more susceptible to it [ 10 ]. Studies on breast, cervical, and ovarian cancer patients showed that those patients had a high prevalence of depression and anxiety disorders [ [11] , [12] , [13] , [14] ]. Nevertheless, depression is often neglected, and the majority of cancer patients do not receive adequate treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%